Resveratrol Analogues as Selective Estrogen Signaling Pathway Modulators: Structure–Activity Relationship - Paulina Kobylka; Malgorzata Kucinska; Jacek Kujawski; Dawid Lazewski; Marcin Wierzchowski; Marek Murias (Molecules, 2022)
Resveratrol is a plant-derived phytoalexin found in grapes, red wine and many other plants used in Asian folk medicine. It is extensively studied for pleiotropic biological activity. The most crucial are anticancer and chemopreventive properties. Resveratrol has also been reported to be an antioxidant and phytoestrogen. The phytoestrogenic activity of resveratrol was assayed in different in vitro and in vivo models. Although these works brought some, on the first look, conflicting results, it is commonly accepted that resveratrol interacts with estrogen receptors and functions as a mixed agonist/antagonist. It is widely accepted that the hydroxyl groups are crucial for resveratrol’s cytotoxic and antioxidative activity and are responsible for binding estrogen receptors. In this work, we assayed 11 resveratrol analogues, seven barring methoxy groups and six hydroxylated analogues in different combinations at positions 3, 4, 5 and 3′,4′,5′. For this purpose, recombined estrogen receptors and estrogen-dependent MCF-7 and Ishikawa cells were used. Our study was supported by in silico docking studies. We have shown that, resveratrol and 3,4,4′5′-tetrahydroxystilbene, 3,3′,4,5,5′-pentahydroxystilbene and 3,3′,4,4′,5,5′-hexahydroxystilbene may act as selective estrogen receptor modulators.